Synthesis of standard functions and generic Ex-OR module using layered T gate. (2017) - Mukherjee, Chiradeep; Panda, Saradindu; Mukhopadhyay, Asish Kumar; Maji, Bansibadan
The quantum-dot cellular automata (QCA) which is the most promising technology in the paradigm of nano electronics has already been claimed to possess ultra-high packing density, high clocking speed and extremely low power dissipation. This work proposes a novel design of high fan-in exclusive-OR gate by using the layered T Gate of QCA. The 'robustness analysis' of layered T gate has also been done to focus the advantage of layered T architecture in generic sense considering the defects of QCA. The synthesis of 'three-literal standard functions' by using layered T gate reports an average 29.31% less area requirement as compared to the best reported design so far. Primarily two-input layered T exclusive OR shows 18.75% less cell requirement and 6.20% less area requirement as compared to the conventional two-input exclusive OR designs. Finally, two-input layered T exclusive OR module extends its design methodology to implement high fan-in exclusive OR gate designs with proper formulation of O-Cost and delay in QCA.